An introduction to the study of William Blake - Plowman, Max, 1883-1941 (Atlantic, 1994)
The book is an excellent exposition of Blake's poetry. It will help the readers to understand and enjoy the poets vision. The book will be found of great interest by the students of English literature, researchers and the general readers. the author is a well known authority on the subject of the book.